2015
DOI: 10.1007/s00198-015-3414-5
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral fat body mass have a protective effect on osteopenia or osteoporosis in adults and elderly?

Abstract: Since both obesity and osteoporosis are public health problems worldwide, strategies aimed at preventing both conditions should be encouraged during aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Inconsistent with that, several studies stated AFM had no24 or a negative25 relationship with BMD. Freitas et al 26 showed that central fat was positively associated with BMD and regarded as an independent and protective factor for the presence of osteoporosis or osteopenia. Sharma et al 27 reported that a bigger trunk (central) FM was associated with increased BMD in the total hip and femoral neck, regardless of HIV status in women.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent with that, several studies stated AFM had no24 or a negative25 relationship with BMD. Freitas et al 26 showed that central fat was positively associated with BMD and regarded as an independent and protective factor for the presence of osteoporosis or osteopenia. Sharma et al 27 reported that a bigger trunk (central) FM was associated with increased BMD in the total hip and femoral neck, regardless of HIV status in women.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there exist studies that have shown that weight and high BMI are positively associated with BMD, while other studies have shown that body fat percentage influences BMD negatively [28]. Central or peripheral body fat mass have been reported to be inversely associated with BMD [29]. Visceral fat has also been reported to have negative impact on trabecular bone mass [30].…”
Section: Discussionmentioning
confidence: 99%
“…31 However, the relation of obesity with osteoporosis has been questioned and several studies have supported an aggravating role of obesity in osteoporosis. [32][33][34][35] Unfortunately, neither DEXA nor BIA-ACC ® could estimate obesity-related qualitative changes of the muscle and bone architecture.…”
Section: Discussionmentioning
confidence: 99%